ANALYSIS OF FUEL CONSUMPTION SENSITIVITY IN FORESTRY ROAD TRANSPORT - Guimarães, Pompeu Paes; Arce, Julio Eduardo; Lopes, Eduardo da Silva; Fiedler, Nilton Cesar; Robert, Renato César Gonçalves; Seixas, Fernando - (Floresta, 2019)
The objective of this work was to analyze how the variation of traveled distance, operational speed, journey time and net cargo transported influence the fuel consumption of vehicles in forest road transport. The data were collected in this operation, covering the area between the regions of Campo do Tenente (forest unit) and Piên (industrial unit), in the state of Paraná. We analyzed the partial elements, loaded trip and empty trip, as well as the total transport cycle (loading, unloading and travel). Using the same mechanical tractor, two vehicular compositions were studied, an articulated vehicle (truck tractor + semitrailer + trailer) and a conjugated vehicle (truck tractor + semitrailer). The vehicle telemetric system was used to perform the data collection of travel time, traveled distance, speed average and fuel consumption of the both vehicles. The results showed that the higher fuel consumption occurred in the loaded trips for longer distances. The sensitivity of fuel consumption was mostly influenced by was traveled distance, so it is recommended the use of vehicles of less load capacity for shorter distances.